Robustness of antiadhesion between nanofibers and surfaces covered with nanoripples of varying spatial period - Buchberger, Gerda; Meyer, Marco; Plamadeala, Cristina; Weissbach, Margret; Hesser, Günter; Baumgartner, Werner; Heitz, Johannes; Joel, Anna-Christin (Frontiers in Ecology and Evolution, 2023)
Since nanofibers have a high surface-to-volume ratio, van der Waals forces render them attracted to virtually any surface. The high ratio provides significant advantages for applications in drug delivery, wound healing, tissue regeneration, and filtration. Cribellate spiders integrate thousands of nanofibers into their capture threads as an adhesive to immobilize their prey. These spiders have antiadhesive nanoripples on the calamistrum, a comb-like structure on their hindmost legs, and are thus an ideal model for investigating how nanofiber adhesion can be reduced. We found that these nanoripples had similar spacing in the cribellate species Uloborus plumipes, Amaurobius similis, and Menneus superciliosus, independent of phylogenetic relation and size. Ripple spacing on other body parts (i.e., cuticle, claws, and spinnerets), however, was less homogeneous. To investigate whether a specific distance between the ripples determines antiadhesion, we fabricated nanorippled foils by nanosecond UV laser processing. We varied the spatial periods of the nanoripples in the range ~203 - 613 nm. Using two different pulse numbers resulted in ripples of different heights. The antiadhesion was measured for all surfaces, showing that the effect is robust against alterations across the whole range of spatial periods tested. Motivated by these results, we fabricated irregular surface nanoripples with spacing in the range ~130 - 480 nm, which showed the same antiadhesive behavior. The tested surfaces may be useful in tools for handling nanofibers such as spoolers for single nanofibers, conveyor belts for producing endless nanofiber nonwoven, and cylindrical tools for fabricating tubular nanofiber nonwoven. Engineered fibers such as carbon nanotubes represent a further candidate application area.